Suplementación proteica con Heno de Guásimo (Guazuma uknifolia) en ovinos de pelo. (1996)
The objetive of this study was to determine the effect of guásimo hay Guazuma ulmifolia as a supplement on the diary profit and the increased weight in hair sheep Ovis ac/es for a balanced diet in protein, energy and dry matter (D.M.), in the Guayaquil, country of Coyaima (Tolima) Colombia, located on altitude of 390 masl, with an average of temperature of 28° C. the annual precipitation average of 1.499 mm, and relative humidic of 69%, in Bs-T. (Holdnidge. 1982). The study include 12 hair sheep in a cross-over desing with 2 treatments Ti and T2 in three evaluations periods. The treatment Ti of protein was supplied with guásimo hay, and T2 treatment was used soybean Glycinemax. There were not important differences ( P <0.05) for the diary profit and the increased weight when diets as treatments Ti and T2 are supplied. As well as, the results showed that use of guasimo hay as a protein supply gives nutritional quality like a diet with soybean.